0542 Pediatric Obstructive Sleep Apnea and Poor Appetite. (25th May 2022) - Tah, Sumeer; Modi, Meet; Brennan, Christine; Rangan, Pooja; Castro, Walter; Lee-Iannotti, Joyce; Rihawi, Anas; Knobbe, Kirstin
Abstract: Introduction: Obstructive Sleep Apnea (OSA) has many impacts on homeostasis. In pediatrics, there have been links observed between health problems and OSA including failure to thrive, obesity, and behavioral disorders. Existing literature evaluates the links between excess weight, obesity, and OSA. However, there is a lack of research exploring the association between OSA and reduced appetite as a contributor to failure to thrive in the pediatric population. In this study, we hypothesized there is a positive correlation between OSA severity and the presence of poor appetite. Methods: We analyzed data retrospectively through medical records of 155 pediatric patients (age < 18 years old) who were diagnosed with OSA by pediatric criteria via polysomnography from April through November 2021. Data was collected from a pre-completed questionnaire done by the guardian or child during the sleep study intake. Poor appetite symptoms were ranked on a Likert scale of occurring "never", "rarely", "occasionally", "frequently", "regularly", or "don't know." The presence of poor appetite symptoms was compared to the severity of pediatric OSA diagnosed during the sleep study. Pearson chi-squared test and Spearman's correlation coefficient were calculated on the data sets. Results: Of 155 patients, 33 (21.3%) were diagnosed with mild OSA, 70 (45.2%) with moderate OSA, and 52 (33.5%) with severe OSA based on pediatric criteria. A total of 53 patients reported poor appetite occasionally, frequently, or regularly. 29.4% of patients with mild OSA reported poor appetite, along with 45.7% of patients with moderate OSA, and 21.2% of patients with severe OSA. Of all patients who reported poor appetite, 60.3% had moderate OSA. However, there was a non-statistically significant correlation between apnea hypopnea index (AHI) and the presence of poor appetite symptoms, Spearman's correlation coefficient of -0.1044 (p-value 0.1960). Conclusion: Overall our data did not show a significant correlation between OSA severity and poor appetite symptoms. There was an association between poor appetite and moderate OSA, however this data is limited by selection bias as 45.2% of patients were categorized as moderate OSA. Further studies are needed, including analyses with similar size populations of each OSA severity category. Support (If Any):